Characteristics of secondary droplets produced by a single drop impacting on a static liquid film. (October 2019) - Li, Jianxin; Zhang, Huang; Liu, Qianfeng
Highlights: A single drop with different Weber number impacting on a static liquid film of different thickness is recorded by a high-speed camera. A series of image pre-processing procedures are performed to detect and extract the secondary droplets from the image. The evolution of the secondary droplet number, diameter and velocity are carried out. The effect of Weber number and the dimensionless film thickness on the features of the secondary droplets is investigated. Abstract: In this paper, an experimental study of the generation of secondary droplets produced by a single droplet impacting on a static liquid film is studied. Different factors are investigated through a high-speed camera at 5000 fps, such as the Weber number of the falling droplet, and the dimensionless liquid film thickness. Several technics are used to improve the image quality to detect the secondary droplets. Especially, a particle tracking algorithm is developed to calculate the velocity distribution of the secondary droplets. The influence of time, Weber number and dimensionless film thickness on the number, diameter and velocity distribution of the secondary droplets are performed. The results show that as time increases, the number of the secondary droplets rises up in the dimensionless time with the range of 0 <  τ  < 2, then decreases during the rest time regardless the Weber number and the dimensionless film thickness. The maximum value of the diameter distribution of the secondary droplets becomes higher, and the range of the velocity distribution becomes narrower over time. As increasing the Weber number, the number of secondary droplets grows up, as well as the peak value of the diameter distribution. Also, the increase of Weber number has a slight effect on the width of the velocity distribution of the secondary droplets. The results also show that, after the droplets impacting on liquid film with different thickness, the number of the secondary droplets changes little at different film thickness. Additionally, the dimensionless film thickness does not have a strong effect on the diameter distribution or the velocity distribution of the secondary droplets.